Beyond sustainability: is government obliged to increase economic benefit from fisheries in the face of industry resistance?. (February 2017) - Emery, Timothy J.; Gardner, Caleb; Hartmann, Klaas; Cartwright, Ian
Abstract: Substantial economic opportunities have been identified in many Australian fisheries but may remain unimplemented due to the perception that the role of government is to ensure harvests are biologically sustainable, while economic decisions should be left to the commercial industry. This paper explores the role of government in driving changes that increase revenue and profit from fisheries (termed economic benefit). Australian fisheries resources are managed by eight different jurisdictions. While each have separate legislation, there is invariably a responsibility to manage on behalf of, and to the benefit of the public, who are the owners of the resource. This paper uses case studies to explore how government can struggle to determine the public interest, separate this from private interests and then implement management changes to ensure the public utility is maximised. Common problems were: (i) overarching economic objectives, which define who should benefit, were often ambiguous and open to interpretation; (ii) the public interest was usually abstract and often under-represented in decision-making processes, (in contrast to industry, who have direct representation); (iii) special interest groups were often able to lobby against changes; and (iv) government was often reluctant to seize opportunities to increase economic benefit when there was significant industry opposition to management changes. In drawing attention to these challenges and how they have been overcome historically, it is argued that government has both a role and requirement under their legislative objectives to take the lead in implementing measures that increase the economic benefit from Australian fisheries. Highlights: There is a gap in current and optimal economic performance of Australian fisheries. Opportunities to increase economic benefit are often resisted by sections of industry. Government may struggle to implement changes in an absence of industry agreement. Case studies examined why proposed economic measures often remained unimplemented. Government must take the lead in implementing measures to increased economic benefit.